2015
DOI: 10.1038/ctg.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CA19-9 Is Associated With Increased Mortality In A Prospective Cohort Of Hepatocellular Carcinoma Patients

Abstract: Objectives:Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related deaths worldwide. CA19-9 is a glycoprotein that predicts poor prognosis in pancreatic and biliary malignancies. We evaluated it as a prognostic biomarker for patients with HCC.Methods:We prospectively enrolled 145 patients with HCC, diagnosed using American Association for Study of Liver Diseases criteria, between October 2008 and November 2012. We examined whether baseline serum CA19-9 levels predicted overall survival. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…However, the study only included patients with liver transplantation and did not exclude patients with ICC or cHCC-CC. Hsu et al [8] investigated 145 cases of HCV-related HCC and found that an elevated serum CA19-9 level of ≥ 100 U/ml is an independent predictor of poor OS. However, 59% (85/145) of the HCC patients had underlying hepatitis C virus, and only 16% had hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study only included patients with liver transplantation and did not exclude patients with ICC or cHCC-CC. Hsu et al [8] investigated 145 cases of HCV-related HCC and found that an elevated serum CA19-9 level of ≥ 100 U/ml is an independent predictor of poor OS. However, 59% (85/145) of the HCC patients had underlying hepatitis C virus, and only 16% had hepatitis B virus.…”
Section: Discussionmentioning
confidence: 99%
“…It is also frequently elevated in patients with combined HCC-cholangiocarcinoma. Elevated preoperative serum CA19-9 levels have been reported to be associated with worse survival in HCC patients who had undergone resection (> 27 U/mL) or liver transplantation (> 100 U/ml) [8][9][10]. However, most of these studies mainly included patients with HCVrelated HCC who underwent resection or transplantation, and the underlying mechanism by which CA19-9 in uences prognosis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although CA 19-9 expression is also related to unfavorable prognosis in some kinds of cancer, why high CA 19-9 predict shorter OS is not understood [34, 35]. We therefore investigated the relationship between CA 19-9 IHC positivity and pathological findings in patients with stage I lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…CA19-9 is used primarily in combination with other biomarkers (e.g., CEA) for the monitoring and management of pancreatic cancer [ 90 ]. CA19-9 is also currently recognised as one of the most common tumour markers for colorectal, gastric, and hepatocellular cancer [ 97 ]. The latter three types of cancer contribute to 28% and 16% of cancer-associated deaths in males and females, respectively ( Figure 1 ).…”
Section: Clinically Approved Biomarkersmentioning
confidence: 99%